Guggulsterone-Mediated Enhancement of Radiosensitivity in Human Tumor Cell Lines - Choudhuri, Rajani; DeGraff, William; Gamson, Janet; Mitchell, James B.; Cook, John A. (Frontiers in Oncology, 2011)
Purpose: To observe the effect of Guggulsterone (GS) on the radiation response in human cancer cell lines. Materials and methods: The radiation response of cancer cells treated with GS was observed by cell survival studies, cell growth assay, NF-κB activity assay, western blotting of some key growth promoting receptors, the DNA repair protein γH2AX, and flow cytometry for DNA analyses. Results: GS inhibited radiation induced NF-κB activation and enhanced radiosensitivity in the pancreatic cell line, PC-Sh. It reduced both cell cycle movement and cell growth. GS reduced ERα protein in MCF7 cells and IGF1-Rβ protein in colon cancer cells and pancreatic cancer cells and inhibited DNA double strand break repair following radiation. Conclusions: GS induced radiation sensitization may be due to several different mechanisms including the inhibition of NF-κβ activation and reductions in IGF1-Rβ. In addition, GS induced γH2AX formation, primarily in the S phase, indicates that DNA double strand breaks in the S phase may be another reason for GS induced radiosensitivity. ERα down-regulation in response to GS suggests that it can be of potential use in the treatment of estrogen positive tumors that are resistant to tamoxifen.